What will the fall semester bring, a new normal?. Issue 6 (18th September 2020) - Miles, David
Abstract : As I sit in my office and write this article, I am thinking about how the world of security has changed since early March. Since March, we have had no students on campus, no sporting events, and a commencement that was held virtually.